PENGEMBANGAN MEDIA VIDEO MENGGUNAKAN APLIKASI ADOBE PREMIERE DAN VIDEOSCRIBE PADA PEMBELAJARAN MATEMATIKA - Muhammad Iqaf Ishaq; Cut Morina Zubainur; Khairul Umam (Universitas Syiah Kuala, 2020)
The integration of science and technology in mathematics learning can be done through learning videos. Various applications can be an option to develop the required learning videos. Adobe Premiere and VideoScribe application is one alternative application that can produce more interesting and diverse videos, but learning videos using these applications are limited. This study describes the process and results of developing valid learning video media using Adobe Premiere and VideoScribe applications on System of Linear Equation with Two Variables (SLETV). This research is Research and Development research. The data sources of this research were validators with expertise in content, construct, and technology. The instrument used to obtain research data was a validation sheet. The results were two videos: The standard form SLETV and the SLETV Solution Method. The development process of the learning videos using Adobe Premiere and VideoScribe applications on SLETV was carried out through the stages of searching for references related to SLETV and applications used to develop videos to design prototypes. The prototypes were then validated and revised until the video media was declared valid. The results showed that the learning videos using Adobe Premiere and VideoScribe applications on SPLDV material were valid for aspects of content, constructs, and technology media. However, the learning videos with Adobe Premiere and VideoScribe applications on SLETV material need to be tested to measure the practicality of the video.